2011
DOI: 10.2147/ijn.s24160
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable inhibitory effects of hybrid liposomes on growth of human colon cancer cells through induction of cell cycle arrest along with apoptosis

Abstract: Background Hybrid liposomes can be prepared by simply sonicating a mixture of vesicular and micellar molecules in buffer solutions. In this study, we investigated the effects of hybrid liposomes on the growth of human colon cancer cells in vitro. Methods Hybrid liposomes (HL-n, n = 21, 23, 25) composed of L-α-dimyristoylphosphatidylcholine (DMPC) and polyoxyethylene( n ) dodecyl ethers (C 12 (EO) n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…While this possibility remains unexplored in PFAAs, other compounds with hydrophobic properties have been shown to induce cell cycle arrest and apoptosis of human colon cancer [70] and other tumor cells [71]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this possibility remains unexplored in PFAAs, other compounds with hydrophobic properties have been shown to induce cell cycle arrest and apoptosis of human colon cancer [70] and other tumor cells [71]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, PFOS and PFOA are also surfactants, characterized by strong hydrophobic properties [ 69 ], which could, in turn, contribute to a protective effect against CRC. While this possibility remains unexplored in PFAAs, other compounds with hydrophobic properties have been shown to induce cell cycle arrest and apoptosis of human colon cancer [ 70 ] and other tumor cells [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bare liposomes not loaded with drug have been shown to arrest cells in G0/G1 phase and induce apoptosis, though obviously the delivery of a drug by liposomes results in altered cellular responses 58–60 . Roa et.al 61 reported that glucose-capped gold nanoparticles accelerate cells through the G0/G1 phase, and arrest them in G2M (much like cisplatin).…”
Section: Abnormal Membrane Proteins Play Pivotal Roles In Platinum-bamentioning
confidence: 99%